Indigenous Ecofeminism? Decolonial Practices and Indigenous Resurgence in Lee Maracle’s Works - López-Serrano, Lucía (Canada and Beyond: A Journal of Canadian Literary and Cultural Studies, 2023)
Ecocritical and ecofeminist studies have frequently borrowed from Indigenous epistemologies to conform new approaches to human-nature relations, particularly now that the pressing climate crisis is making western societies contemplate the need for radical solutions. As Leanne Betasamosake Simpson remarks, “the western academy is now becoming interested in certain aspects of Indigenous Knowledge” such as “Traditional Ecological Knowledge (TEK)” (373). However, the scope of this interest is reduced and disconnects ecological knowledge from decolonial practices, such as land claims or Indigenous feminisms. Maile Arvin et al. emphatically support that “settler colonialism has been and continues to be a gendered process” (8) and thus its ramifications and effects (upon nature or Indigenous communities) cannot be detangled without an Indigenous feminist perspective. In this article, I focus on an ecocritical analysis of several works by Lee Maracle, who dedicated her career to the regeneration and revalorization of Indigenous systems of knowledge, in order to pinpoint the intersections between feminism, decolonization, and nonhuman ecological thinking that might develop into a potential Indigenous ecofeminism that truly recognizes Indigenous epistemologies in their full context. Basing myself off Nishnaabeg scholar Leanne Betasamosake Simpson’s theories on Indigenous radical resurgence, which assert that a cultural resurgence (such as a revalorization of Indigenous ecological knowledge) cannot take place without a political resurgence (such as the acknowledgement of Indigenous sovereignty), I argue that Maracle’s portrayal of natural elements and her imagining of human-nature relations is inextricably linked to a decolonizing perspective foregrounded on Indigenous feminism.